Measurement of the Z boson differential production cross section using its invisible decay mode (Z → νν¯¯¯) in proton-proton collisions at s√ = 13 TeV - Jayananda, M.K.; Sonnadara, D.U.J.; Wickramaratne, D.D.C. (My University, 2021)
Abstract: Measurements of the total and differential fiducial cross sections for the Z boson decaying into two neutrinos are presented at the LHC in proton-proton collisions at a center-of-mass energy of 13TeV. The data were collected by the CMS detector in 2016 and correspond to an integrated luminosity of 35.9 fb−1. In these measurements, events are selected containing an imbalance in transverse momentum and one or more energetic jets. The fiducial differential cross section is measured as a function of the Z boson transverse momentum. The results are combined with a previous measurement of charged-lepton decays of the Z boson. The measured total fiducial cross section for events with Z boson transverse momentum greater than 200 GeV is 3000+180 −170 fb.
Keywords: Hadron-Hadron scattering (experiments), Lepton production, Particle and resonance production